Estimación de los modelos TAR cuando el proceso del ruido sigue una distribución t (2011)
In this paper, TAR models with t noise is considered. A Bayesian procedure for estimation is developed when the model has been identiﬁed, that is, the structural parameters have been estimated. The method consists in ﬁnding the conditional posterior densities and use the Gibbs sampler. Simulated example shows that this methodology leads good estimates of the parameters.